Best practices in Icelandic crisis communication during volcanic eruptions: development of a tentative framework - Bergþóra Njála Guðmundsdóttir 1969- (2016)
The objective of this study is to investigate what practices have been successful and what practices need improvement in official communication prior to, during and after volcanic eruptions in Iceland. Furthermore, to analyse to what extent previously identified best practices within the crisis communication literature are applicable to the Icelandic situation. A qualitative interview research was conducted on experiences of public information officers, experts, spokespersons and crisis managers as well as journalists working during the Bárðarbunga seismic activity and the Holuhraun eruption in Iceland that started in August 2014 and ended in February 2015. It revealed nine elements that are considered important and/or successful in communication efforts during recent eruptions, here suggested as a tentative framework for best practices in crisis communication in Iceland. The study underlines that Icelandic crisis communication practices need to consider the special Icelandic conditions which are characterized by scarce resources; a greater need for improvisation in the crisis communication process; a great international media interest; close contact with and good access to the local media; a sense of closeness to the public; and the importance of cooperation between various institutions. Furthermore, the need for proactive communication is prominent in the digital landscape of modern society.